2019
DOI: 10.1002/ecs2.2848
|View full text |Cite
|
Sign up to set email alerts
|

Secondary succession has surprisingly low impact on arboreal ant communities in tropical montane rainforest

Abstract: Understanding forest regeneration processes is increasingly important as disturbed forests spread rapidly in tropical landscapes. While successional dynamics are relatively well-understood for plants, they remain poorly known for tropical insects, particularly in montane rainforests and tree canopies. We studied the effect of montane forest succession on arboreal ant communities in New Guinea near their natural elevational limit (1800 m a.s.l.). We censused ant species and nests in replicated 0.1-ha plots of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 64 publications
0
20
0
Order By: Relevance
“…Our study has demonstrated that vegetation structure and its differential use by ant species can contribute to the elevational patterns in tree-nesting ant richness, abundance and community structure. We comprehensively sampled all nests in all trees in forest plots, an approach previously used to explore the effects of forest succession, but not a forest elevational gradient (Klimes et al 2012, Mottl et al 2019. We found a strong mid-elevation peak in nest abundance and species richness, and there, in the largest trees species co-occurred more than expected by chance.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our study has demonstrated that vegetation structure and its differential use by ant species can contribute to the elevational patterns in tree-nesting ant richness, abundance and community structure. We comprehensively sampled all nests in all trees in forest plots, an approach previously used to explore the effects of forest succession, but not a forest elevational gradient (Klimes et al 2012, Mottl et al 2019. We found a strong mid-elevation peak in nest abundance and species richness, and there, in the largest trees species co-occurred more than expected by chance.…”
Section: Discussionmentioning
confidence: 91%
“…inside myrmecophytic bulb plants such as Hydnophytum and Myrmecodia, or under the roots of mosses, orchids and ferns) as present on the supporting tree. Nests were categorized into 12 types based on nest locations (microhabitat sites), where they were found within each tree: 'on trunk base', 'under epiphyte roots', 'cavity/gallery in trunk', 'carton/soil/silk on leaves', 'under bark', 'on bark', 'in/under liana', 'myrmecophytic epiphyte', 'cavity/ gallery in live branch', 'cavity/gallery in live twig', 'in dead/ rotten branch' and 'in dead/rotten twig' (Klimes et al 2012, Mottl et al 2019. We recorded the distance in metres of the nest from ground level (nest height hereafter), and estimated nest size on an ordinal scale (1: ≤ 100 workers, 2: 100-500 workers, 3: 500-1000 workers 4: > 1000 workers).…”
Section: Study Sites and Sampling Methodsmentioning
confidence: 99%
“…This non‐linearity can probably be attributed to the distribution of microhabitats, some of which were found only on large‐canopy trees, or trees with numerous lianas or epiphytes (Klimes, 2017). Indeed, microhabitat richness was found to be the main driver for the pattern in arboreal ant communities in other extensive whole‐forest studies (Klimes et al ., 2015; Mottl et al ., 2019; Plowman et al ., 2019). A similar pattern of tree biomass affecting the abundances of arboreal arthropods has also been observed in specialist herbivores feeding only on a single tree genus or species (Novotny et al ., 2006, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Basset et al ., 2012), plot‐based censuses can become a useful tool to assess the abundances of arthropods and improve our understanding of habitat‐ and temporal‐driven changes. For example studies of whole‐forest arthropod communities have already revealed the contrasting effect of forest age on leaf‐chewing communities (Redmond et al ., 2018) and tree‐dwelling ants (Mottl et al ., 2019), suggesting the importance of microhabitats for ants. In the light of recent reports of a worldwide decline in insects (Basset and Lamarre, 2019), the need to understand the processes underpinning arthropod ecology becomes increasingly important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation